A simple strategy to design 3-layered Au-TiO2 dual nanoparticles immobilized cellulose membranes with enhanced photocatalytic activity. (1st March 2020) - Yu, Yuqing; Zhu, Xingrong; Wang, Langrun; Wu, Fengshou; Liu, Shilin; Chang, Chunyu; Luo, Xiaogang
Graphical abstract: Highlights: Cellulose membrane-based photocatalyst was fabricated by suction filtration method. The photocatalyst had a good degradation performance of 94.99 % for RhB. Au NPs on the surface of TiO2 -CM could enhance the light absorption band range. Photo-charge separation efficiency was improved to enhance photocatalytic activity. Abstract: Cellulose-based photocatalysts of supported nanoparticles feature high photocatalytic activity but their facile construction and photocatalytic mechanism exploration are highly challenging. Herein, a simple structural design principle and synergistic properties of 3-layered porous cellulose-based membranes are used for catalytic degradation of Rhodamine B in an aqua system. The 3-layered Au-TiO2 cellulose membranes were fabricated through the tape method and the suction filtration process. The composite membranes with strong redox ability, high charge-separation efficiency, and wide absorption range could stimulate the solar-driven plasma evaporation of Au nanoparticles and the photocatalytic function of TiO2 nanoparticles simultaneously. As characterized by Scanning Electron Microscopy, well-defined Au nanoparticles with an average size of 18.24 ± 3.17 nm were uniformly distributed on the TiO2 -CM surface. Compared with TiO2 -CM, TiO2 -Au-CM showed better catalytic degradation of organic dye. This work demonstrated that a simple strategy design of Au-TiO2 -CM could efficiently enhance the photocatalytic activity for the degradation of dyes in water.